2020
DOI: 10.1108/ijcst-06-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively evaluating the effects of flash fire exposure on the mechanical performance of thermal protective clothing

Abstract: Purpose The purpose of this paper is to determine the effect of flash fire exposure on the mechanical properties of single-layer thermal protective clothing. Design/methodology/approach The full-scale flame manikin tests were performed to simulate flash fire exposure. Two typical fire-resistant fabrics were investigated. The manikin was divided into seven body parts and the specimens meeting the requirements of tensile and tear strength standards were sampled. Fabric thickness, mass per unit area, tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The effects of flash fire on the mechanical properties of single layer thermal protective fabrics have been examined [19]. Similar kinds of results were found; the heat flux significantly affected the mechanical properties of the thermal protective fabrics [19].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…The effects of flash fire on the mechanical properties of single layer thermal protective fabrics have been examined [19]. Similar kinds of results were found; the heat flux significantly affected the mechanical properties of the thermal protective fabrics [19].…”
Section: Introductionmentioning
confidence: 66%
“…However, the thermal protective performance did not change considerably as a consequence of changes in the mechanical properties [8]. The effects of flash fire on the mechanical properties of single layer thermal protective fabrics have been examined [19]. Similar kinds of results were found; the heat flux significantly affected the mechanical properties of the thermal protective fabrics [19].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The thermal aging of Kevlar/PBI blends was attributed to the change of a crystallite size crystalline lattice of Kevlar and random chain scissions of PBI [55]. A full-scale flame manikin study revealed the complicated effects of garment structure on thermal degradation of thermal-protective clothing [56]. Numeric simulation also indicated that the heat transfer in the air space was more complicated on the garment level than the fabric, because of the varying relative positions between different body segments and the heat source, as well as the ventilation openings [57].…”
Section: Discussionmentioning
confidence: 99%